Analysis of quasi-lattice distributions of statistics from finite population - Turkuvienė, Jurgita; Bikelis, Algimantas (Lietuvos matematikos rinkinys, 2004)
Edgeworth expansions are used for approximation of quantiles, estimation of parameters, construction of confidence intervals and testing hypothesis. Paper shows how to construct ` ` long’’ Edgewort asymptotic expansions.